Implikasi Pembangunan Fasilitas Pariwisata terhadap Lingkungan Fisik di Kawasan Sempadan Pantai Yeh Gangga Tabanan, Bali - Widiastra, I Made; Rajendra, I Gusti Ngurah Anom; Kastawan, I Wayan (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment), 2019)
Sempadan pantai (a waterfront setback which by law is reserved and in which development is restricted) of Yeh Gangga Beach at the Tabanan Regency-Bali has been increasingly well used. This area is supposedly protected and dedicated to public uses, as outlined by Local Government Regulation number 11, year 2012. Unfortunately, the government has not yet been effectively imposing this policy. There is a growing concern, if the uncontrolled used of sempadan pantai is perpetuated, it will affect the nature of this reserved area. This study aims to determine the impact of the construction of tourist facilities on the sempadan of Pantai Yeh Gangga. The analysis is grounded by conceptions offered by several literatures relevant to tourism development and environmental protection. This study uses a qualitative research method. Data is collected through observations, photographic documentation, and interviews with community leaders, government authorities, employers and tourists. The collected data is presented in the form of tables and narratives. Study results show that development of tourist facilities on Yeh Gangga's setback area has various negative impacts on the physical environment. This research strongly recommends local government to carry out a routine control over waterfront development. Alternatively, this can be done by empowering local communities and enforcing sanctions when violations over an enforced regulation take place. Local communities are strongly advised to preserve the natural state of their physical environment by not polluting it. Business owners should also participate in this move by conducting environmentally conscious business-practices and taking adequate premeditated protections of the environment in their hand at all chances. Keywords: coastal development, environment, law enforcement, Yeh Gangga   Abstrak Sempadan Pantai - kawasan yang berfungsi utama sebagai kawasan lindung - di Pantai Yeh Gangga, Kabupaten Tabanan, Bali mengalami perkembangan pemanfaatan yang pesat. Area ini seharusnya dilindungi dan dimanfaatkan untuk kepentingan publik seperti halnya yang diatur oleh Peraturan Daerah Nomor 11 Tahun 2012. Akan tetapi Pemerintah Daerah Tabanan belum epektif memberlakukan kebijakan ini. Apabila ini terus berlangsung, maka akan tumbuh bangunan ilegal dan akan sulit ditertibkan. Penelitian ini bertujuan untuk mengetahui dampak pembangunan fasilitas pariwisata terhadap lingkungan fisik kawasan sempadan Pantai Yeh Gangga. Teori kepariwisataan dan lingkungan digunakan dalam pendekatan kajian ini. Dengan menggunakan metode kualitatif, data dikumpulkan melalui observasi bertahap, dokumentasi langsung, wawancara dengan tokoh masyarakat, pemerintah, pengusaha. Penyajian data dilakukan dengan dokumentasi, dalam bentuk tabel dan narasi. Hasil penelitian menunjukkan pembangunan fasilitas pariwisata di kawasan sempadan Pantai Yeh Gangga Tabanan berdampak negatif terhadap aspek lingkungan fisik. Rekomendasi penelitian ini adalah pemerintah daerah harus melakukan pengawasan secara rutin dengan memberdayakan masyarakat setempat dan bertindak tegas terhadap pelanggaran. Masyarakat setempat agar memprioritaskan kelestarian lingkungan fisik dengan tidak mencemari lingkungan. Pengusaha dan industri pariwisata dalam menjalankan bisnis harus juga menjaga lingkungan. Kata kunci: pembangunan pesisir, lingkungan, penegakan aturan,Yeh Gangga